Bioqueries: a collaborative environment to create, explore and share SPARQL queries in Life Sciences - García-Godoy, María Jesús; López-Camacho, Esteban; Navas-Delgado, Ismael; Aldana-Montes, José Francisco (My University, 2016)
Bioqueries provides a collaborative environment to create, explore, execute, clone and share SPARQL queries (including Federated Queries). Federated SPARQL queries can retrieve information from more than one data source.
Keywords: Bases de datos relacionales; Linked Data